Savings without sacrifice: a case report on open-source textbook adoption. (2nd September 2018) - Clinton, Virginia
ABSTRACT: Rising textbook costs have prompted the development of open-source textbooks to increase access to education. The purpose of this case report is to examine open-source textbook adoption through the COUP framework (costs, outcomes, use, and perceptions) comparing a semester with a commercial textbook to a semester with an open-source textbook. Students ( N  = 520) were enrolled in an undergraduate course at a mid-sized public university in the United States. Results indicated that although costs were substantially lower, student learning outcomes and perceptions of quality were similar or better with an open-source textbook. Although students were much more likely to access the open-source textbook electronically, there were no differences in how they reported using the two textbooks to support their learning. Considering the financial savings of open-source textbooks, these findings build on existing empirical support that encourage the adoption of open-source textbooks.